Causes of and possible solutions to poverty among women in Uganda - Syslová, Markéta; Sejkora, Jiří, 1985-; Kohut, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Poverty remains one of the most critical global challenges, with Sub-Saharan Africa continuing to face high poverty rates and extreme inequality. Among the most vulnerable groups affected by poverty are women, who endure compounded disadvantages due to structural, social, and cultural barriers. This thesis examines the causes of and potential solutions to poverty among women in Uganda, a low-income country in Sub-Saharan Africa, with a focus on agriculture, malnutrition, and education. Women in Uganda, despite their significant role in agriculture, face lower productivity and income than men, largely due to gender inequality, limited access to land, and insufficient agricultural technologies. Malnutrition, particularly anemia, further exacerbates poverty, with women and children being disproportionately affected by undernutrition. Additionally, persistent gender gaps in education, including early pregnancies and child marriages, hinder women's access to educational opportunities, thereby limiting their future prospects. The thesis is divided into three chapters: the first outlines the general causes of female poverty in sub-Saharan Africa, focusing on gender disparities in agriculture, malnutrition, and education; the second explores potential regional solutions for addressing these issues; and the third presents a detailed analysis of Uganda's specific challenges, policies, and practices aimed at tackling the identified causes. By examining these interconnected factors, the thesis aims to contribute to the understanding of poverty among women in Uganda and provide recommendations for targeted interventions to reduce it.
Vedoucí práce: Jiří Sejkora
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses